Application Status of Carbon Nanotubes in Fire Detection Sensors - Xiao, Guoqing; Weng, Hengxiang; Ge, Liang; Huang, Qi (Frontiers in Materials, 2020)
With the rapid development of the city, all kinds of high-rise buildings, large shopping malls and entertainment places have been built one after another. There are some hidden dangers of fire accidents. Effective prevention and monitoring of fire is the focus of fire prevention and control field. As the information source of fire prevention and control, the preparation of fire detection sensor with high sensitivity and short response time is of great significance for fire prevention and monitoring. At present, the commonly used fire detection sensors mainly include CO sensor, temperature sensor and flame sensor. With the development of material technology in recent years, especially the development of carbon nanotube technology, a new fire detection sensor represented by carbon nanotube materials has emerged. In this paper, the research progress of carbon nanotubes in fire detection sensors is reviewed. The applications of carbon nanotubes in CO detection, flame light detection and temperature detection are discussed in detail. Finally, the development trend of fire detection sensors based on carbon nanotubes is proposed, and the development direction of fire detection sensors in the Internet of things is prospected.